2021
DOI: 10.3389/feduc.2020.618075
|View full text |Cite
|
Sign up to set email alerts
|

A Call for Rethinking Schooling and Leadership in the Time of COVID-19

Abstract: COVID-19 forced a sudden closure of schools, prompting a hasty and unplanned reaction of educators to deliver educational content. Inspired by Ivan Illich's book Deschooling Society, where he argues for the delivery of educational content by utilizing technology and forging intentional partnerships with parents and communities to assist in the delivery of educational content, we reflect on how these ideas impact school leadership and preparation of school leaders. This “forced” deschooling has offered educator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Home-school partnerships developed overnight allowed teachers and parents to become co-partners in providing a remote learning platform through their homes (Gurr, 2020; Gurr and Drysdale, 2020). For some schools, the infrastructure at school needed to be immediately upgraded to deliver this kind of learning, in other schools, parents struggled with not having sufficient devices, wi-fi or the technical know-how to help their children learn online (Rincones et al ., 2021). As one principal described, “The school has made a huge leap because technologically we weren't advanced as a school.…”
Section: Theoretical Discussion Of Findingsmentioning
confidence: 99%
“…Home-school partnerships developed overnight allowed teachers and parents to become co-partners in providing a remote learning platform through their homes (Gurr, 2020; Gurr and Drysdale, 2020). For some schools, the infrastructure at school needed to be immediately upgraded to deliver this kind of learning, in other schools, parents struggled with not having sufficient devices, wi-fi or the technical know-how to help their children learn online (Rincones et al ., 2021). As one principal described, “The school has made a huge leap because technologically we weren't advanced as a school.…”
Section: Theoretical Discussion Of Findingsmentioning
confidence: 99%
“…Finally, in light of these findings, it needs to be discussed whether and how traditional school improvement and school effectiveness research needs to adapt to reflect the adaptive challenges represented by the pandemic. Prior research has indicated, for example, that COVID-19 has created an unprecedented crisis with numerous and ongoing challenges to educational systems around the world (Rincones et al, 2021). These challenges required both adaptive and contingent leadership, including targeted responses to the social, emotional, mental health and academic needs of students and school staff (e.g., Moss et al, 2020;Cordeiro et al, 2021;Greany et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…School infrastructures such as the internet connection, computers, and other teaching devices had become one of the biggest challenges during the pandemic crisis (Rincones et al, 2021). To most participants, the poor Internet connection became one of the most significant challenges when working during the pandemic crisis.…”
Section: School Infrastructurementioning
confidence: 99%